A molecular anchor for stabilizing triple-helical DNA. - Fox, K R (1995)
Molecular modeling has been used to predict that 2,6-disubstituted amidoanthraquinones, and not the 1,4 series, should preferentially interact with and stabilize triple-stranded DNA structures over duplex DNA. This is due to marked differences in the nature of chromophore-base stacking and groove accessibility for the two series. A DNA foot-printing method that monitors the extent of protection from DNase I cleavage on triplex formation has been used to examine the effects of a number of synthetic isomer compounds in the 1,4 and 2,6 series. The experimental results are in accord with the predicted behavior and confirm that the 1,4 series bind preferentially to double- rather than triple-stranded DNA, whereas the isomeric 2,6 derivatives markedly favor binding to triplex DNA.